PROGRAM PEMBERDAYAAN MASYARAKAT PESISIR BERBASIS PENDIDIKAN DI SAUBEBA-ABUN PAPUA BARAT - Pattiselanno, F.; Wondikbo, A.; Emaury, A.; Farwas, A.; Rumayomi, I.; Towansiba, N. (Buletin Udayana Mengabdi; Vol 17 No 1 (2018): Buletin Udayana Mengabdi, 2018)
Since 2010, Universitas Papua - UNIPA in particular the Research and Community Services Department was involved in survey, outreach program and collaboration works with people in Saubeba as a part of Leatherback conservation program. To follow up the work of UNIPA, between June and August 2016, a group of student from UNIPA conducted a field work in Saubeba, Abun District of Tambrauw Regency with special concerned on 11 programs that have been planned together with the communities. Agriculture, Agricultural Product Processing, Education, Environment and Health as well as Leatherback Conservation were prioritized as essential programs. This paper provides part of the program that conducted in collaboration witth local communities in order to support education-based of coastal communities empowerment.